Manual therapy, stretching, and strength exercise on patients with tension-type headache – Multiple case study - Capalonga, Lucas; Lagemann, Nadine Gabriela; Grave, Magali Teresinha Quevedo (Headache Medicine, 2022)
Introduction Tension-type headache (TTH) has been considered the most common primary headache in adults, characterized by the presence of bilateral pain, presenting in the form of pressure or tightness (non-pulsating), with intensity ranging from mild to moderate. Objectives To analyze the medium-term effects of manual therapy techniques, stretching and muscle strengthening exercises on functionality, pain and disability in patients with TTH. Methods The following variables were evaluated: pain through the Visual Analog Scale (VAS); the strength of the cervical musculature through dynamometry; the disability by the Neck Disability Index (NDI); and the impact of headache on activities of daily living (ADL) through the application of the Headache Impact Test (HIT-6) before and after the intervention. Six physiotherapy sessions were performed, once a week, for six weeks. Results There was a reduction in the post-intervention pain pattern (4.2 ± 2.3 vs. 0.2 ± 0.5; p=0.019). In terms of disability, there was a difference between the pre- and post-intervention periods (11.4 ± 1.5 vs. 6.6 ± 2.3; p=0.022). In addition, after the intervention, there was a reduction in HIT-6 levels when compared to the pre-intervention period (51.0 ± 7.5 vs. 59.6 ± 3.9; p=0.038). Conclusion The physical therapy intervention protocol proved to be effective in reducing the pattern of pain, disability, and headache impact on ADL of patients with TTH.